A interpretação constitucional dos princípios da afetividade e solidariedade familiar pelos tribunais superiores brasileiros - Torres, Claudia Vechi (2014)
The Brazilian juridical ordain has suffered several transformations on Family Law as of the 1988 Federal Constitution, which incorporated the changes in socio-cultural values and behaviors that appeared in the post-modern Brazilian society, with the repersonalization of the family, beginning with the principles of human dignity, affectivity and familiar solidarity; occurring an enlargement of the concept of family, increasing the relevance of socioaffectivity and eudaimonia. The general purpose of this dissertation is to analyze the constitutional interpretations of paradigmatic cases of the Brazilian Superior Courts checking the conditions and behaviors required to achieve the principles of affectivity and familiar solidarity. To do so, uses an exploratory and descriptive research trough books, scientific papers, jurisprudence, monographs and consult to specialized magazines to identify the reasons and specific purposes of the principles of affectivity and family solidarity within the constitutional norms, systematizing the primary meaning of these principles, then to observe the trial of patriotic courts, the criteria and standards of behavior used in their application. The analysis of recent decisions of the Supreme Federal Court and the Superior Court of Justice on the topic of the familiar relations, utilizing the new interpretative approach to the law that considers man as an ontological being of language, demonstrate that the affectivity and familiar solidarity are constitutional principles concretized in decisions, that don’t affect the principle of protection of the juridical security, that is, don’t cause uncertainty despite the incipient specification of criteria to its use